Education with Animation Video and Flyer Improving Pregnant Women Behavior of Sleep Hygiene: Which One More Effective? - Asih, Fransisca Retno; Pondaang, Mytha Febriany; I’anah, Fauzah Cholashotul (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2024)
No study related to sleep hygiene education with digital technology for pregnant women in Indonesia has been conducted. This study aims to determine the differences in the effect of education with animated videos and digital flyers on increasing pregnant women's sleep hygiene behavior. This quasi-experimental study was conducted on 108 who pregnant women were selected and assigned consecutively to the animation video and flyer groups and received education on sleep hygiene for 18 days. The validated behavior questionnaires was completed by both groups. Mann-Whitney U and Wilcoxon tests were used for the analysis. The mean (SD) behavior score was 69 (13.3) and 86.2 (11) in the video group and 68 (8.7) and 76.8 (10.5) in the flyer group on the first and 19th days, so there was a significant difference in terms of sleep hygiene behavior between the animation video and flyer group on the 18th day (p 0.000). Pregnant women who had sleep hygiene education with an animation video had more behavioral enhancement than flyer (20.5 11.5). Sleep hygiene education with an animation video as a first-line strategy is important and more effective in preventing insomnia.